Globalization and the Good Corporation: A Need for Proactive Co-existence - Sethi, S. Prakash (Journal of business ethics, 2003)
Large corporations are coming under intense pressure to act in a socially responsible manner. Corporations have accepted this notion provided that it is exercised voluntarily. It has also been argued that corporations can do well by doing good, and that good ethics is good business. This paper presents an alternative viewpoint by demonstrating that while voluntary socially responsible conduct is desirable, it plays a rather small role in inspiring good corporate conduct. Instead, (a) it is the external economic-competitive conditions that define the parameters and opportunities for good corporate conduct; and (b) the values and traditions of the corporations, and their perceived risk in exploiting those opportunities, that influence the extent of a corporation's socially responsible conduct. The framework presented here analyzes certain market-competitive conditions, which determine the scope and direction of socially responsible corporate conduct, and the instruments available to society to enhance ethical corporate conduct. It suggests that from society's perspective, we should move away from the notion of corporate social responsibility and toward corporate social accountability. Most modern economies operate under conditions of imperfect competition where corporations gain above-normal profits, i.e., market rent, from market imperfections. Therefore, corporations should be held accountable for a more equitable distribution of these above-normal profits with other groups, e.g., customers, employees, etc., who were deprived of their market-based gains because of market imperfections and corporate power. Three approaches are suggested for measuring corporate accountability through corrections. These are: information imbalance, bargaining power imbalance, and, adjudication, remedy and relief imbalance.